Sikap Wanita Usia Subur dalam Melakukan Deteksi Dini Kanker Serviks melalui Dukungan Suami - Putu Indah Sintya Dewi; Putu Wahyu Sri Juniantari Sandy; Dewa Ayu Carma Krisna Dewi (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the relationship between the husband's support and the attitudes of women of childbearing age in the early detection of cervical cancer through the IVA test in the Sawan I Public Health Center. The method used in this research is non-experiment, which studies with correlational descriptive research design. The results showed that the p-value was 0.0001. In conclusion, there is a relationship between the husband's support and the attitudes of women of childbearing age in the early detection of cervical cancer in the Sawan I Community Health Center. Keywords: Husband's Support, Cervical Cancer, IVA Test, Fertile Age Women